Properties of Charcoal Briquettes from Charcoal Scraps Mixed with Spent Coffee Grounds as An Alternative Fuel - Komhom, Sataporn (Journal of Advanced Development in Engineering and Science, 2024)
The objective of this research was to analyze the properties of charcoal briquettes produced using charcoal scraps after burningbiomass materials through a selection of sieves smaller than 2.36 mm, mixed with spent coffee grounds discarded from steam-pressurized coffee machines, dried at 110 oC for 24 h. The experiment was designed by varying the weight ratio of charcoal scraps, coffee grounds, and starch glue at a concentration of 5% by weight and comparing all samples without glycerin and with glycerin mixed into starch glue. After analyzing the properties of the charcoal briquettes, the results showed that the weight ratio of charcoal scraps to coffee grounds was 3:1 and 3:2 by mixing glycerin into the starch glue as a possible condition for producing charcoal briquettes with suitable properties. It had a surface area of 7.95 and 4.97 m2/g, a density of 467.36 and 484.09 kg/m3, a fracture percentage of 2.22% and 1.45%, and a heating value of 23.43 and 21.84 MJ/kg, respectively. A test of heating 500 g of water withfour charcoal briquettes found that the 3:1 and 3:2 weight ratios mixed with glycerin revealed the highest temperatures of 71 and 66 oC, respectively,and both samples had an additional heating time of approximately 20 mincompared to samples with the same weight ratio without glycerin added.